2023
DOI: 10.1155/2023/6639030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nonthermal Plasma on Shear Bond Strength of Translucent Zirconia in Layering Ceramic

Abstract: Background. Today, various methods are used to increase the bond strength of zirconia in layering ceramics. This study evaluated the effects of nonthermal argon plasma on zirconia shear bond strength to layering porcelain. Materials and Method. In this experimental study, 42 square blocks of zirconia were prepared and randomly divided into three groups (n = 14) according to the applying surface treatment: (1) the control group (without any surface treatment), (2) the plasma-treated group with argon nonthermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Moreover, the sandblasting pressure of 0.28 MPa (indicated by the manufacturer) was not sufficient to obtain a homogeneous TSC layer [52]. Furthermore, García-de-Albeniz et al (2023) [53] reported a direct relationship between the pressure of airborne particle abrasion, the amount of silica layer over zirconia, smaller particle size during sandblasting procedures, and an increase in bond strength after cementation [54,55], suggesting that pressure and particle size are critical for achieving higher bond strength results, as well as the type of surface treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the sandblasting pressure of 0.28 MPa (indicated by the manufacturer) was not sufficient to obtain a homogeneous TSC layer [52]. Furthermore, García-de-Albeniz et al (2023) [53] reported a direct relationship between the pressure of airborne particle abrasion, the amount of silica layer over zirconia, smaller particle size during sandblasting procedures, and an increase in bond strength after cementation [54,55], suggesting that pressure and particle size are critical for achieving higher bond strength results, as well as the type of surface treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research has been conducted to improve the surface treatment methods for these materials. Techniques such as plasma irradiation [ 18 , 19 ], sandblasting [ 20 , 21 ], tribochemical coating [ 22 , 23 ], laser abrasion [ 24 , 25 ], and chemical etching [ 26 , 27 ] have been examined for their ability to modify material surfaces for better bonding with luting agents. Among these methods, chemical etching with hydrofluoric acid (HF) is notable for its efficiency in etching silica-containing materials [ 17 , 28 ] such as lithium disilicate glass, feldspathic porcelain, polymer-infiltrated ceramic networks, and resin composites.…”
Section: Introductionmentioning
confidence: 99%